Difficulties and opportunities of the development of trade relations between Russia and the EU - Krasavina, Polina; Bolotov, Ilya; Kohut, Dominik; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
Russia and the European Union have been important trade partners for almost 25 years, since they signed the Partnership and Cooperation Agreement in 1997. Nevertheless, throughout the whole history of their partnership numerous disagreements have arisen between the partners, which affected their biliteral trade. In my bachelor thesis I examine the impact of geopolitical instability on trade between Russia and the EU. Chapter 1 provides information on historical development of their trade relations and describes legal basis for economic cooperation. Chapter 2 analyzes the current state, difficulties, and opportunities of trade relations, including impact of the Ukrainian crisis of 2014 and Covid-19 crisis. Chapter 3 examines the state of trade and economic relations with Russia’s three biggest trade partners in the EU: Germany, the Netherlands and Italy.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses